Réponses

2013-12-12T07:09:04+01:00
1)  D= e ³ x (e-²) puissance 4 x e ÷ e-1
D= e^3 x e ^(-2 x ( 4xe/ e^-1)
D = e^3 x e ^( -2x 4 x e^2)
D = e^3 x e ( - 8 x e^2)
D = e ^( 3 x (-8) x e^2) = e^( -24 x e^2)
D = 1/ e^(24 e ^2)
 E= (e³) puissance 4 x e-² ÷e puissance 5
E= e ^12 x e^-2  / e^5
E = e ^10 / e^5
E = e^5

2013-12-12T08:04:51+01:00
1)  D= e ³ x (e-²) puissance 4 x e ÷ e-1
e^a puissance b =  e ^ab
D= e^3 x e ^(-2 x ( 4xe/ e^-1)
D = e^3 x e ^( -2x 4 x e^2)
D = e^3 x e ( - 8 x e^2)
 e^a *e^b = e^ab
D = e ^( 3 x (-8) x e^2) = e^( -24 x e^2)
D = 1/ e^(24 e ^2)
 E= (e³) puissance 4 x e-² ÷e puissance 5
E= e ^12 x e^-2  / e^5
E = e ^10 / e^5
E = e^5